Drugs of abuse drive neurotransmitter plasticity that alters behavior: implications for mental health - Pratelli, Marta; Spitzer, Nicholas C. (Frontiers in Behavioral Neuroscience, 2025)
Neurotransmission is a complex process with multiple levels of regulation that, when altered, can significantly impact mental health. Neurons in the adult brain can release more than one transmitter and environmental stimuli can change the type of transmitter neurons express. Changes in the transmitter neurons express can generate changes in animal behavior. The ability of neurons to express multiple transmitters and/or switch them in response to environmental stimuli likely evolved to provide flexibility and complexity to neuronal circuit function in an ever-changing environment. However, this adaptability can become maladaptive when generating behavioral alterations that are unfit for the environment in which the animal lives or the tasks it needs to perform. Repeated exposure to addictive substances induces long-lasting molecular and synaptic changes, driving the appearance of maladaptive behaviors that can result in drug misuse and addiction. Recent findings have shown that one way drugs of abuse alter the brain is by inducing changes in the transmitter neurons express. Here, we review evidence of prolonged exposure to addictive substances inducing changes in the number of neurons expressing the neuropeptide orexin, the neuromodulator dopamine, and the inhibitory transmitter GABA. These findings show that drug-induced transmitter plasticity is conserved across species, that addictive substances belonging to different classes of chemicals can induce the same type of plasticity, and that exposure to only one drug can cause different neuronal types to change the transmitter they express. Importantly, drug-induced transmitter plasticity contributes to the long-term negative effects of drug consumption, and it can, in some cases, be either prevented or reversed to alleviate these outcomes. Regional neuronal hyperactivity appears to modulate the appearance and stabilization of drug-induced changes in transmitter expression, which are no longer observed when activity is normalized. Overall, these findings underscore the importance of continuing to investigate the extent and behavioral significance of drug-induced neurotransmitter plasticity and exploring whether non-invasive strategies can be used to reverse it as a means to mitigate the maladaptive effects of drug use.